Living Rome (Lever Press, 2026)
Living Rome: Space, Identity, and the Politics of Belonging looks beyond the romanticized image of Rome, towards a kaleidoscopic view of the city shaped by inequalities, socio-political challenges, and acts of resistance and solidarity. In the wake of urban developments related to migration, housing shortages, COVID-19, crime, and other social changes, this volume offers a grounded approach, mapping the contemporary realities of Italy’s capital from a variety of methodological standpoints. Contributors argue that the unseen fringes, both geographically peripheral and those embedded within the very heart of Rome, are crucial for understanding its social dynamics. These ‘hidden’ geographies foster vibrant communities, challenge ideas of home and belonging, and act as key sites of creativity, resistance and everyday life. Bringing together urban sociologists, anthropologists, geographers, demographers, criminologists, decolonizing and feminist scholars, this study contributes to a growing body of research on the city and its social movements, aiming to inform policy and contribute to a more just and sustainable Rome. Using a variety of methods, from quantitative cartography and policy analysis to (auto)ethnography and creative methodologies, this volume speaks well beyond Rome, to conversations about cities worldwide.